Effectiveness of various finite element analysis method for the dynamic cornering fatigue test of an automotive wheel - Poungkom, Vana; Pimsarn, Monsak (My University, 2024)
The automotive wheel is an indispensable part of a motor vehicle as it is the first part that receives loads in various forms from applications such as falls, heavy cargo and cornering, etc. This paper presents the effectiveness of the analysis process using a finite element method to simulate the dynamic cornering fatigue test by comparing the experimental results with the finite element analysis (FEA) results obtained from three methods: full transient, modal transient and static structural methods. The static structural method was found to have the highest accuracy, with less than 2% error, and also the least computational time. It takes 97% less computational time than the full transient method. Therefore, this paper demonstrates that the static structural method is most effective in using the fatigue life analysis to improve design prior to actual testing to help reduce the cost and time of launching new products in the alloy manufacturing industry.
Keywords: Dynamic cornering fatigue test; full transient; modal transient; static structural; wheel